The Ideas that Conquered the World : Peace, Democracy, and Free Markets in the Twenty-First Century - Mandelbaum, Michael (New Dehli Viva Books, 2008)
Continuing in the same tradition as Francis Fukuyama's </The End of History/>, political science professor (and senior fellow of the Council on Foreign Relations) Mandelbaum continues the argument that capitalism and democracy are inextricably linked and that so-called "free markets" have emerged as indisputably triumphant in the world of contesting political and economic ideas. In exploring the political affairs of the United States, Europe, the Middle East, Russia, and China, he advances two propositions about liberal democracies that may seem surprising to observers of the current international scene: that democracies tend to conduct peaceful foreign affairs and that free markets naturally lead to democracy. One of America's leading foreign policy thinkers offers a major new statement about global politics in the 21st century, and shows how prevailing trends are remarkably favorable to the United States and the nations of the West.
Include Notes and Index
Keywords: World politics -- Post-communism -- Cold War (1945-1989)